(untitled) (Journal of Educational Sciences, 2016)
In the article the author considers the essence of education in the context of pedagogical theories. The author stresses that education equips a system of intellectual and practical skills and abilities that enable him to solve any problems in his life and professional activity. In the process of receiving education, a person develops and самосовершенствовается. In the course of education a person accumulates experience of creative activity, necessary for the decision of various problems of life and activity, and all of this is displayed in the content of education. The author stresses that in the context of the knowledge society, the development of the education system acquires a crucial role to ensure the successful development of the country. The modern paradigm of education implies the creation of dynamically developing education system, using modern technologies and ensuring the achievement of the objectives of the future. In connection with this change model of education. Thus, the earlier models were idealized, focused on the social, cultural and educational values. It means the level of development of the modern society makes to higher education higher requirements; satisfy that with the positions of the University model, formed in the ХІХ century, it is impossible. Therefore, the fundamental functions of a classical University in the 90 years in the ХХ century. The twentieth century was subjected to rethink and was greatly expanded. The author considers the development of models of education in the world of comparative aspect and the Genesis of formation of «the classical University» in the context of the philosophical and pedagogical views on the nature of education.